Effects of Silicone Mattress Combined with Hydrocolloid Dressing on Pressure Ulcers and Phlebitis in ICU Patients with Liver Failure. (15th April 2022) - Chen, Suhong; Wang, Yonggang; Huang, Shun; Wu, Dan; Li, Yinyin; Zhong, Zhiqiang; Xue, Yajin; Li, Huanxin; Mu, Jinsong
Abstract : Objective. This study was aimed at clarifying the application effect of silicone mattress combined with hydrocolloid dressing in ICU patients with liver failure. Methods. A total of 86 patients with liver failure admitted to the intensive care unit (ICU) of the Fifth Medical Center of Chinese PLA General Hospital from September 2018 to September 2020 were selected as the research subjects. Patients treated with conventional sponge mattress and routine nursing care were included in group A (n = 43 ), and those treated with silicone mattress combined with hydrocolloid dressing were included in group B (n = 43 ). The incidence of pressure ulcers and phlebitis, the scores of Visual Analogue Scale (VAS) and Pittsburgh Sleep Quality Index (PSQI), and the nursing satisfaction were observed and compared between the two groups. Results. The incidence of pressure ulcers in group B (6.98%) was lower than that in group A (25.58%). The incidence of phlebitis in group B was lower than that in group A (20.93% vs. 53.49%). The VAS score of group B was 2.16 ± 0.38, which was lower than that of group A (4.86 ± 1.09). The PSQI score of group B was lower than that of group A (9.74 ± 2.76 vs. 14.84 ± 3.95 ). A higher nursing satisfaction was determined in group B compared with group A (93.02% vs. 76.74%). Conclusions. Silicone mattress combined with hydrocolloid dressing can reduce the incidence of pressure ulcers and phlebitis in ICU patients with liver failure, reduce complications, and improve nursing satisfaction, which is worthy of clinical promotion.